2018
DOI: 10.3389/fimmu.2018.00164
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Signaling: A Targetable Checkpoint Limiting Development of the Antitumor Immune Response

Abstract: An immune response must be tightly controlled so that it will be commensurate with the level of response needed to protect the organism without damaging normal tissue. The roles of cytokines and chemokines in orchestrating these processes are well known, but although stress has long been thought to also affect immune responses, the underlying mechanisms were not as well understood. Recently, the role of nerves and, specifically, the sympathetic nervous system, in regulating immune responses is being revealed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 206 publications
(174 reference statements)
6
109
0
2
Order By: Relevance
“…To our knowledge, our group first reported that mouse models of cancer and antitumor immunity (39)(40)(41), immune responses in graft versus host disease (42), dendritic cell biology (43), and radiosensitivity of hematopoietic stem cells (44) are each significantly influenced by room temperature. These are representative of a growing number of papers reporting how choice of housing temperature impacts experimental outcomes and reproducibility in several mouse models of disease and we have recently reviewed this topic (45)(46)(47). Since these reviews were published, similar effects on mouse models of Alzheimer's disease (48), osteoporosis (49), fatty liver disease (50), and asthma (51) have also been reported.…”
Section: Housing Temperatures For Mice Affect Chronic Adrenergic Strementioning
confidence: 98%
“…To our knowledge, our group first reported that mouse models of cancer and antitumor immunity (39)(40)(41), immune responses in graft versus host disease (42), dendritic cell biology (43), and radiosensitivity of hematopoietic stem cells (44) are each significantly influenced by room temperature. These are representative of a growing number of papers reporting how choice of housing temperature impacts experimental outcomes and reproducibility in several mouse models of disease and we have recently reviewed this topic (45)(46)(47). Since these reviews were published, similar effects on mouse models of Alzheimer's disease (48), osteoporosis (49), fatty liver disease (50), and asthma (51) have also been reported.…”
Section: Housing Temperatures For Mice Affect Chronic Adrenergic Strementioning
confidence: 98%
“…In our study, PPN anti-OSA activity was related to direct cytostatic effects and cell cycle arrest, decreasing survival and mitosis in β-AR expressing tumor tissue. However, SNS activation and β-adrenergic signaling can regulate a wide range of cancer-associated molecular pathways via both direct effects on β-AR expressing transformed cells and regulation of other β-receptor-bearing cells populating the complex tumor stroma, such as vascular or immune cells [47,48]. In spite of using T cell-de cient nude mice for our in vivo studies, this animal model still has a robust innate immune response involving dendritic cells, tumor-associated macrophages and natural killer cells, which are known to play a key role against OSA [49].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to immunotherapy developing in some initially responding tumors is now a clinical problem. Some evidence demonstrated that adrenergic stress inhibits immune response and its blockage might increase therapeutic efficacy of immunotherapy [98]. It was already studied that beta-adrenergic blockers reduced PC-related mortality [99].…”
Section: Neural Tme As a Potential Therapeutic Targetmentioning
confidence: 99%